Increased foot strike variability in Parkinson's disease patients with freezing of gait. (August 2018) - Shah, Jesal; Pillai, Lakshmi; Williams, David K.; Doerhoff, Shannon M.; Larson-Prior, Linda; Garcia-Rill, Edgar; Virmani, Tuhin
Abstract: Introduction: Freezing of gait (FOG) is a debilitating, late motor complication of Parkinson's disease (PD) that occurs in 50–80% of patients. Gait freezing significantly worsens quality of life by decreasing mobility and increasing falls. Studies have shown that patients with episodic freezing episodes also have deficits in continuous gait. We evaluated whether there was an objective gait correlate to the increased stumbling reported by many patients with gait freezing. Methods: PD subjects and healthy controls (HC) were enrolled after IRB approval. Subjects with more than 1 fall/day or a Montreal Cognitive Assessment score <10 were excluded. Subjects walked at their normal pace, 8 lengths of a 20 × 4 foot pressure-sensor mat. Data was collected and analyzed using PKMAS software (Protokinetics) and statistical analysis performed using SPSS 22 (IBM). Results: 72 age matched subjects (22 PD FOG, 27 PD no-FOG, and 23 HC) were enrolled. Disease duration and Hoehn & Yahr scores were not significantly different between the PD groups. Mean dimensions of foot strike were not significantly different between groups, but PD FOG subjects had increased step-to-step variability in foot strike as measured by the percent coefficient of variation (%CV) in foot strike length compared to PD no-FOG and HC, independent of stride velocity. In PD no-FOG subjects, fallers also had higher variability in foot strike length compared to non-fallers. Conclusion: PD subjects with FOG had increased variability in foot strike suggesting that in addition to stride length variability, foot strike variability could contribute to imbalance leading to falls. Highlights: Freezing of gait leads to decreased mobility and falls in Parkinson's disease. Patients with gait freezing report stumbling even when medicated with levodopa. We find increased variability in foot strike in patients with freezing of gait. Increased foot strike variability also occurred in subjects reporting falls. Foot strike variability could contribute to imbalance leading to falls.